Value Added Tax in Nepal: Structure, Performance and Challenges - Neupane, Bharat (Journal of Rapti Babai Campus, 2026)
This article analyses the design, development and performance of Value Added Tax (VAT) in Nepali fiscal system. Nepal introduced VAT on November 16, 1997 to replace sales tax, entertainment tax, hotel tax and contract tax in the country; it is a major step towards implementing modern broad-based consumption taxes to combat resource scarcity and enhance revenue elasticity. The paper analyses the evolution of tax system in Nepal, comparing direct and indirect tax systems and presenting main methods of calculating VAT: addition, subtraction and the method of tax credit - being implemented in Nepal at present. Although, hypothetically, the least discretionary tax would also be able to correct a balance- of-payment deficit state of affairs and optimize both policy objects, the paper identifies important practical challenges. These make for administrative incompetence, political insecurity and non-transparency. The results indicate that, even if VAT is still a preferable option to general sales tax, its effectiveness will depend on the implementation of effective administrative reform and professional integrity.